The influence of institutional ownership, executive characteristics, and fixed asset intensity on tax avoidance - Alamsyah, Cindy Alvionita; Romadhina, Anggun Putri (Educoretax, 2025)
This study aims to analyze the effect of Institutional Ownership, executive characteristics, and fixed asset intensity on tax avoidance in companies listed in the LQ-45 index on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. and then The data used are secondary data obtained from audited financial statements and annual reports. The sample was selected using a purposive sampling technique based on specific criteria relevant to the research objectives. As a result, 9 companies met the criteria over five consecutive years, yielding 45 total observations. Data analysis was conducted using panel data regression with a common effect model, supported by EViews version 13 software. The results show that simultaneously, Institutional Ownership, and executive characteristics, and fixed asset intensity significantly affect tax avoidance. Partially, Institutional Ownership and executive characteristics have a significant impact on corporate tax avoidance, while fixed asset intensity does not show a significant effect. These is findings suggest that institutional ownership and executive leadership play important roles in shaping tax management strategies. In contrast, the proportion of fixed assets held by a company may not directly influence tax avoidance behavior. This study is expected to provide both theoretical and practical contributions for policymakers, tax authorities, corporate management, investors, academics, and future researchers. A better understanding of the factors influencing tax avoidance particularly in large companies listed in the LQ-45 index can support improved tax compliance, stronger governance, and more effective regulatory oversight in Indonesia’s capital market.